Justice and Ethics in Business Law: A Legal Philosophy Perspective - Kurniawan, I Gede Agus; Samsithawrati, Putu Aras; D. Tee-anastacio, Princess Alyssa (Faculty of Law, Universitas Pattimura, 2025)
Introduction: In the business world, law plays a crucial role as a guideline that maintains stability and justice. However, its implementation often benefits parties with significant influence, necessitating an approach that considers moral and ethical aspects to achieve true justice.Purposes of the Research: Explore and analyze how the principles of justice and ethics rooted from the perspective of legal philosophy are applied in the practice of business lawMethods of the Research: This study employs a normative legal research method with a conceptual approach, examining legal norms, principles of distributive and commutative justice, and ethical responsibilities in business based on primary and secondary legal sources.Results Main Findings of the Research: The findings reveal that the principles of justice and ethics in legal philosophy are applied in business law practice by prioritizing distributive and commutative justice, as well as ethical responsibility toward society. Distributive justice seeks to ensure fair business competition and equal opportunities for business actors, while commutative justice guarantees equality of rights and obligations through fair contracts. However, significant challenges remain in implementing justice and business ethics in Indonesia, including weak oversight, the dominance of large corporations, and low awareness of social responsibility.